In and out of refugia: historical patterns of diversity and demography in the North American Caesar's mushroom species complex. Issue 23 (20th November 2015) - Sánchez‐Ramírez, Santiago; Tulloss, Rodham E.; Guzmán‐Dávalos, Laura; Cifuentes‐Blanco, Joaquín; Valenzuela, Ricardo; Estrada‐Torres, Arturo; Ruán‐Soto, Felipe; Díaz‐Moreno, Raúl; Hernández‐Rico, Nallely; Torres‐Gómez, Mariano; León, Hugo; Moncalvo, Jean‐Marc
Abstract: Some of the effects of past climate dynamics on plant and animal diversity make‐up have been relatively well studied, but to less extent in fungi. Pleistocene refugia are thought to harbour high biological diversity (i.e. phylogenetic lineages and genetic diversity), mainly as a product of increased reproductive isolation and allele conservation. In addition, high extinction rates and genetic erosion are expected in previously glaciated regions. Some of the consequences of past climate dynamics might involve changes in range and population size that can result in divergence and incipient or cryptic speciation. Many of these dynamic processes and patterns can be inferred through phylogenetic and coalescent methods. In this study, we first delimit species within a group of closely related edible ectomycorrhizal Amanita from North America (the American Caesar's mushrooms species complex) using multilocus coalescent‐based approaches; and then address questions related to effects of Pleistocene climate change on the diversity and genetics of the group. Our study includes extensive geographical sampling throughout the distribution range, and DNA sequences from three nuclear protein‐coding genes. Results reveal cryptic diversity and high speciation rates in refugia. Population sizes and expansions seem to be larger at midrange latitudes (Mexican highlands and SE USA). Range shifts are proportional to population size expansions, which were overall more common during the Pleistocene. This study documents responses to past climate change in fungi and also highlights the applicability of the multispecies coalescent in comparative phylogeographical analyses and diversity assessments that include ancestral species.